Emergency endovascular repair of ruptured visceral artery aneurysms - Sadat, Umar (BioMed Central, 2007)
BACKGROUND: Visceral artery aneurysms although rare, have very high mortality if they rupture. CASE PRESENTATION: An interesting case of a bleeding inferior pancreaticduodenal artery aneurysm is reported in a young patient who presented with hypovolemic shock while being treated in the hospital after undergoing total knee replacement. Endovascular embolization was successfully employed to treat this patient, with early hospital discharge. CONCLUSION: Prompt diagnosis and endovascular management of ruptured visceral aneuryms can decrease the associated mortality and morbidity.